THE TECHNOLOGY OF THE NEW INSTRUMENTAL ESTIMATION METHOD OF THE VEGETATION COVER MICROCLIMATIC CHARACTERISTICS - Dvoretskij, Taras; Kukhtin, Vyacheslav (Proceedings of National Aviation University, 2017)
Purpose: Development and approbation of the program-apparatus complex for the measurement of the basic microclimatic characteristics at the vegetation cover. Methods: The complex allows to measure simultaneously the air temperature and humidity, direct and indirect illumination into the sublayers and over the grass stand with the entry of the findings into the acting permanently storage device. Results: The device features control carried out on the experimental areas with the mire vegetation (Phragmito-Magno-Caricetea class association of the Klika in Klika and Novak 1941) demonstrated the compliance of the declared characteristics with the obtained results. Discussion: The question on the dependency form of the vegetation ecological role in the natural settings has not only practical importance, but vital theoretical significance, as the consequence transformation, in particular, the ecosystems, leads to the limit of their buffer possibilities and to the cessation of work on supporting of the existing soil and atmosphere balances. natural conditions, and under the anthropogenic impact, as well as the measures forming on the base of the obtained results, aimed to their conservation, recovery and inexhaustible use, is important and burning question. The systematic observation carrying out for the environment forming role change of the different ecosystem types under natural conditions, and under the anthropogenic impact, as well as the measures forming on the base of the obtained results, aimed to their conservation, recovery and inexhaustible use, is important and burning question.